Understanding policing of vehicle hijacking in Alexandra Gauteng Province, South Africa: The prospects, challenges and effective responses - Tshoane, Sabelinah Mmabjala (Technium Social Sciences Journal, 2022)
The goals of this research were to evaluate and explain the prospects, challenges and the effective response of the South African Police Service (SAPS) in combating vehicle hijacking. Vehicle hijacking is defined as being “when a person has taken a vehicle through force, violent acts, or the threat of intimidation, a person has committed the crime of vehicle hijacking”. South Africa experiences one of the highest motor vehicle hijacking rates in the world. Although vehicle hijacking is a worldwide phenomenon, it has increased drastically in the Alexandra Township (Gauteng Province—South Africa). The study adopts a qualitative research approach with the intention of striving to grasp an imperative understanding, accompanied by a subjective rationale of the extent and nature of vehicle hijacking, and to evaluate the police strategies in combating vehicle hijacking, thereby also gaining valuable insight and understanding of the underlying contributing factors in the Alexandra policing area. Semi-structured interviews were conducted with twenty-nine (29) participants drawn from the South African police service department, public prosecutors from the Alexandra regional court, community leaders, community members, victims, and perpetrators. Indirect observation, structured and semi-structured interviews were utilised to afford the study an understanding of the extent and nature of vehicle hijacking and its affiliating factors, as provided from the perspective of the participants. The results revealed that the South African Police Service did not have a clear strategy to deal the scourge of vehicle hijacking. Secondly, contributing factors to vehicle hijacking were poverty and unemployment in the Alexandra policing area. Thirdly, illegal firearms, unregistered street mechanics, and scarp yards specifically, appeared to be the main causes of vehicle hijacking. The study recommends that the South African police service members in the Alexandra policing area should adopt effective planning and collaborative problem-solving partnerships. Crime prevention requires the optimal use of their limited resources, and effective partnerships and will increased efficiency. More importantly, the complexity of prevention often requires initiatives and interventions that go well beyond the scope of the mandate and resources of any one organization.